Pengaruh Tunjangan Kinerja, Belanja Modal, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan - Rizki Putra Perdana; Jumansyah Jumansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
This paper aims to examine the effect of performance allowance, capital expenditure, and use of information technology on quality of financial statements at ministry (public sector), as well as to identify which one variable that has dominant effect on quality of financial statements. To examine the effect, we used quantitative methods. We collected primary data through distribution of questioner to 137 work unit from 581 work unit at Kementerian Perhubungan. Data analysed used Multiple Linear Regression. We found that all variable have significant influence simultaneously on quality of financial statements. Performance allowance and use of information technology significantly influence, while capital expenditure does not have effect on quality of financial statements. We can conlude that performance allowance motivates the officer to improve quality of financial statements. The use of information technology also improves quality of financial statement, it means that investment in information technology is right decision.